Mengembangkan Nilai Karakter Kerja Sama pada Siswa Kelas IV Sekolah Dasar Negeri 08 Kota Bengkulu Melalui Ekstrakurikuler Seni Tari Persembahan dalam Rangka Pewarisan Budaya Lokal - Lola Manera; Puspa Djuwita; Bambang Parmadi (UNIB Press, 2023)
The general objective of this research is to describe the development of the character values ​​of cooperation in fourth grade students at SD Negeri 08 Bengkulu City through extracurricular dance offerings in the context of inheriting local culture. This study uses a qualitative research method with a single case study design. The results of the research specifically concluded that dance extracurricular activities form the character values ​​of cooperation carried out in three stages, namely preparation, implementation and assessment. In general, every part of the dance offering, both from the opening, the core and the closing, can develop the character of cooperation, namely helping each other members in the group, appreciating the contribution of each group member, each group member taking turns and sharing tasks, being in a work group when the activity takes place. The two supporting and inhibiting factors in developing the character of cooperation through dance extracurricular offerings in the context of local cultural inheritance include internal factors, namely the lack of awareness and concern for local culture.